2021
DOI: 10.1103/physreva.104.022409
|View full text |Cite
|
Sign up to set email alerts
|

Distillation of genuine tripartite Einstein-Podolsky-Rosen steering

Abstract: We show that a perfectly genuine tripartite steerable assemblage can be distilled from partially genuine tripartite EPR steerable assemblages. In particular, we consider two types of hybrid scenarios: one-sided device-independent scenario (where one observer is untrusted, and other two observers are trusted) and two-sided device-independent scenario (where two observers are untrusted, and one observer is trusted). In both scenarios, we show distillation of perfectly genuine steerable assemblage of three-qubit … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Moreover, what happens when moving from the bipartite to the multipartite scenario? It has been shown that the Greenberger-Horne-Zeilinger and W-type assemblages generated by the corresponding multiparty-entangled types can be distilled by local filter [57]. Can our approach be generalized in recent proposed steering networks [58] or multipartite steering [59]?…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, what happens when moving from the bipartite to the multipartite scenario? It has been shown that the Greenberger-Horne-Zeilinger and W-type assemblages generated by the corresponding multiparty-entangled types can be distilled by local filter [57]. Can our approach be generalized in recent proposed steering networks [58] or multipartite steering [59]?…”
Section: Discussionmentioning
confidence: 99%
“…However, we have obtained a maximum of 4 Eves when each party is performing dichotomic measurements showing an increment from the previous work. On the other hand in biased case when only the measurement corresponding to Eves' σ x measurement is unsharp and each Eve perform some unitary operation before sending the post-measured state to next Eve followed by the particular Alice's measurement (21), we get an unbounded number of Eves. Bob can assure the security of QKD protocol by having higher secret key rate and terminating the protocol in adverse scenario of drop in secret key rate below a threshold value.…”
Section: Discussionmentioning
confidence: 99%
“…Quantum steering [14][15][16][17][18][19][20][21] is an intermediate correlation between entanglement and Bell-nonlocality, was discovered by E. Shrödinger as an interpretation of the famous work by Einstein-Podolsky-Rosen [22]. It is the key resource behind 1S-DIQKD whose security is based on the monogamy of the quantum steering [23].…”
Section: Introductionmentioning
confidence: 99%
“…We refer the reader to see Refs. [63][64][65][66] when the most general cases are considered. Therefore, the effective evolution of W under the superposition scenario can be written as…”
Section: Fig 2 Schematic Illustration Of the Work Extraction Processmentioning
confidence: 99%